Dimensionality reduction of germanium selenide for high-efficiency thermoelectric applications. Issue 12 (15th August 2019) - Ul Haq, Bakhtiar; AlFaify, S.; Laref, A.; Ahmed, R.; M. Taib, M.F.
Abstract: Dimensionality reduction has been proved as a feasible route to enhance the performance of thermoelectric materials for renewable energy applications. In this article, we investigate the effect of dimensions reduction on thermoelectric properties of GeSe using the density functional theory and Boltzmann transport theory based first-principles approaches. These investigations have been carried out for bulk (3D) and three polymorphs of single-layered (2D) GeSe (such as α-GeSe, β-GeSe, and γ-GeSe). Calculations of energetic stability demonstrated the 2D-GeSe as stable as the 3D-GeSe. The arrangement of bands within the electronic band structures of 3D and 2D GeSe showed them as indirect bandgap semiconductors. The β-GeSe and γ-GeSe exhibited wider energy bandgap and consequently large Seebeck coefficients than the 3D-GeSe and α-GeSe. The reduction in structural dimensions stimulated a sharp increase in electrical conductivity and Seebeck coefficient (particularly for β-GeSe and γ-GeSe) which has resulted in large power factor. The room-temperature thermoelectric figure of merit (ZT) of 3D-GeSe, α-GeSe, β-GeSe, and γ-GeSe of magnitude 1.02, 0.83, 1.00, and 1.10 respectively have typically broken the benchmark value of ZT ≈ 1. The ZT of these materials is sensitive to change in temperature and has been recorded as large as 1.72 for γ-GeSe at a low temperature of 150 K. The large power factors and ZT of single-layered GeSe reveal the dimensionality reduction as a feasible approach for enhancing the performance of thermoelectric materials for renewable energy applications.